Implementation of Human Resources Quality Management System at PT. Cosmo Makmur Indonesia - Supriatal Supriatal (International Journal of Sharia Business Management, 2023)
This study aims to determine how much influence the implementation of the quality management system ISO 9001: 2008 clause six concerning human resources has on the performance of employees in the production division at PT. Cosmo Makmur Indonesia. This research is an associative quantitative research. The sample used was 50 people from the results of Slovin's theory calculations. The data collection method uses a primary data system, namely observation and questionnaires and secondary data, namely literature study. The results showed that the implementation of the ISO 9001: 2008 quality management system clause six concerning human resources in the frequency data analysis was perceived as very good at 3.85 and employee performance was very good at 3.88. In the linear regression analysis Y = 12.311 + 0.75X, the perceived correlation coefficient is very strong at 0.944, the coefficient of determination is 89.1%